Addressing the psychology of financial markets - David Tuckett (Economics: The Open-Access, Open-Assessment E-Journal, 2009)
The author suggests that the 2008 financial crisis was the culmination of an accelerating and inherently unstable process of financial market evolution. He argues that markets are not well organized to manage the power that financial assets have to generate emotion and their wider effect on human imagination and judgement, anchored in neurobiology. Judgements and decisions about risk, reward and the evaluation of success can become systematically compromised because the excitement of potential gain is disconnected from anxiety about potential consequences, producing groupthink and bubbles. When anxiety breaks through, a catastrophic loss of confidence is inevitable. In the aftermath the emotional pain that would be involved in accepting responsibility stands in the way of lessons being learned. The author's theoretical framework is influenced by modern psychoanalysis and draws on an interview study of international fund managers in 2007. He suggests that underlying psychological conflicts have influenced the way market institutions have evolved to compete by selling the promise of exceptional performance. To cope with the expectations upon them, agents are impelled to base their actions on stories which overvalue opportunities and underestimate risks; this creates agency issues and facilitates the process of disconnecting anxiety from excitement that creates bubble potential. Policy implications go well beyond improving regulation and transparency.
Keywords: G01; G18; G28; 330; Financial bubbles; financial crises; group functioning; groupthink; market instability; financial regulation; psychoanalysis; psychology; Finanzmarktkrise; Anlageverhalten; Finanzmarkt; Bubbles; Sozialpsychologie; Erwartungstheorie; Regulierung; Welt